(untitled) - Wright, Erik Olin (New York, 2011)
This book evaluate to what degree contemporary American society realizes these values and suggest how Americans might solve some of the social problems that confront America today. It consists of 3 parts: Capitalism; Inequality; Democracy
Keywords: Giá trị xã hội,Social values; Hoa Kỳ,United States